Extracorporeal shock wave lithotripsy effect on renal arterial resistive index changing - Mustafa Hiroš; Lejla Milišić; Amira Mešić; Edin Begić; Emir Milišić; Zlatan Zvizdić; Asmir Jonuzi (Medicinski glasnik, 2018)
Aim: To investigate a correlation between resistive index (RI) level changes following extracorporeal shock wave lithotripsy (ESWL) in treated and non-treated kidneys depending on the ESWL treatment intensity. The study was conducted on 60 subjects, which were divided in two groups according to age and treatment protocol. Results: In the group of patients younger than 55 years of age there was a significant increase in mean RI values, on the first (p=0.001) and second day after the treatment (p=0.007). In the group older than 55 years of age, the resulting increase in mean RI levels was also significant on the first (p=0.003) and second (p=0.011) day following the treatment. The RI values in the non-treated kidney on the first day after the treatment grew significantly (p=0.033). In the group older than 55, RI values in the non-treated kidney grew significantly on the first day after the treatment (p=0.044). In the group who received 2000 SWs, RI levels grew significantly (p=0.044) as well as in the group who received 4000 SWs during the treatment, where the significance was more pronounced (p=0.007). Conclusion: There is a correlation between RI changes and the degree and localization of changes in vascular elements of the kidney. Post-ESWL treatment changes are existent and reversible, over a period of one week after the treatment.
Keywords: treatment; renal circulation; safety